PENGUKURAN TINGKAT KUALITAS ELEMEN PLACEMAKING PADA RUANG TERBUKA PUBLIK KAWASAN TEPI AIR TAPAK KOTA TERNATE MELALUI PENDEKATAN IMPORTANCE PERFORMANCE ANALYSIS - Yoga Adi Nugroho; Muhammad Sani Roychansyah (Universitas Gorontalo, 2022)
Building urban parks in urban areas, especially in waterfront areas with a variety of attractions, is an important strategy to accommodate the many urban activities caused by rapid urbanization and the need for social space, and even small-scale parks can also provide the need for economic services and cultural ecosystems. However, differences in quality regarding performance levels and importance in waterfront urban parks have not been extensively explored. Therefore, this study takes public open spaces scattered in the Tapak area of Ternate City as a case. This is to evaluate the level of space quality from the user's perspective based on the placemaking elements in a city park, using importance and performance analysis. The results show that: Users' perspectives on the importance and performance of open spaces differ significantly, and “Facilities for Recreation” is the sub-element that has the largest gap between willingness and expectation. The spatial and temporal profile of users is the main factor influencing their perspective. Users most agree with the improvement of several placemaking sub-items, namely